2016
DOI: 10.1007/s10854-016-4448-y
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, sintering and properties of CaO–Al2O3–B2O3–SiO2 glass/Al2O3 composites with different CaO contents

Abstract: CaO-Al 2 O 3 -B 2 O 3 -SiO 2 glass/Al 2 O 3 composites for low temperature co-fired ceramics (LTCC) were prepared by tape casting method, and the effects of CaO content on the microstructure, sintering, and properties were discussed. Results showed that an appropriate CaO addition in CABS glass not only efficiently contributed to a dense glass/ceramic body, but also was endowed with better sintering characteristics, more excellent mechanical and dielectric properties. CABS glass/Al 2 O 3 composites with 9 wt% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The traditional method to lower the sintering temperature of the Al 2 O 3 is by glass addition. Several authors reported the effective role of glass in reducing the sintering temperature of Al 2 O 3 …”
Section: Introductionmentioning
confidence: 99%
“…The traditional method to lower the sintering temperature of the Al 2 O 3 is by glass addition. Several authors reported the effective role of glass in reducing the sintering temperature of Al 2 O 3 …”
Section: Introductionmentioning
confidence: 99%
“…The powders settled under the action of gravity forming porous solid bridges in the green sheets . Although fine powder is detrimental to the relative density of the green sheet, it possesses a higher surface energy, which provides a greater driving force for densification …”
Section: Tape Casting Processmentioning
confidence: 99%
“…For example, pure ethyl acetate dries quickly, allowing for good production efficiency, but premature drying creates a skin over the green sheet. This skin can induce streaks or even cracks under the doctor blade . Streicher et al and Gutiérrez et al noted that the evaporation rate of the solvent was the main cause of tape cracking.…”
Section: Tape Casting Processmentioning
confidence: 99%
“…For example, Murata SWG shows a large bending strength, but its thermal conductivity is poor . CaO‐BaO‐Al 2 O 3 ‐B 2 O 3 ‐SiO 2 /AlN and Li 2 O‐SiO 2 ‐ZrO 2 /Al 2 O 3 glass/ceramic composites exhibit high thermal conductivity, but their mechanical strength is low . Therefore, it is necessary to develop new types of glass/ceramic composites that have both high mechanical strength and good thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%